Overseas investments by Singapore listed companies in 1991-1992 - Lim, Kian Yong (2015)
The increasing importance of overseas investments to the growth of Singapore's economy motivated this study on the extent of overseas investments undertaken by listed Singapore companies in the years 1991 and 1992. The profitability of such ventures, together with other related issues were also explored in this study. The results of the study show that for the years 1991 to 1992, there was no significant shift towards higher overseas investments. However, with the recent call to regionalise by the Government, overseas investments are expected to increase in the years to come. The fact that returns from such ventures were found to be promising should serve as an added incentive for companies to invest overseas. Although Australia and New Zealand were identified as the most profitable destinations for investments, most of these investments were found to be channeled into other Asian countries. This focus on countries close to home was because Singapore companies knew the region better than countries farther away. The least popular destinations were found to be the European countries, which experienced negative returns on investments in 1992. With respect to the main industrial sector that invested overseas, the study found that the Food and Beverage sector had the highest level of overseas investments. It was also the most profitable sector, generating the highest rate of return on overseas investments among the sectors. Given the aim of building an external wing to the Singapore's economy, the level of overseas investments so far was found to be inadequate. This may be attributed to the problems faced by companies in investing abroad, which will be identified in this study. Presently, the Singapore Government has taken steps to combat these problems and encourage more overseas investments. A fourteen-member Committee To Promote Enterprise Overseas, comprising of eleven private sector corporate chiefs and three from Government-linked companies has thus been formed in January 1993 for this purpose.